Adhesive Capsulitis: Demographics and Predictive Factors for Success Following Steroid Injections and Surgical Intervention - Brandon J. Erickson, M.D; Yousef Shishani, M.D; Meghan E. Bishop, M.D; Anthony A. Romeo, M.D; Reuben Gobezie, M.D (Elsevier, 2019)
Purpose: Examine demographic factors of all patients treated for adhesive capsulitis by a single surgeon, report the treatments and outcomes of these patients, and determine the effectiveness of various treatments, including corticosteroid injections and operative intervention in relation to risk factors for adhesive capsulitis. Methods: All patients treated for adhesive capsulitis by a single surgeon between 2008 to 2014 with minimum 2 years' follow-up were identified via charts and operative reports and were eligible for inclusion. Demographic information including sex and medical comorbidities was documented. Preintervention and postintervention shoulder range of motion was recorded. Specific treatment information (number of corticosteroid injections, etc) was collected. Treatment outcomes were then compared as an aggregate and among varying comorbidities. Results: Overall, 1377 patients were treated for adhesive capsulitis (946 women vs 431 men [P = .001]). For patients with adhesive capsulitis: a higher percentage of men than women had diabetes (24.8% vs 17.3% [P = .001]); nondiabetic patients had better forward flexion at initial presentation than patients with diabetes (114° vs 108° [P = .015]); more patients with diabetes required capsular release than nondiabetic patients (13% vs 7.3% [P = .003]); more nondiabetic patients resolved adhesive capsulitis without corticosteroid or surgical intervention than patients with diabetes (83.6% vs 61.7% [P = .001]); more nondiabetic patients resolved adhesive capsulitis after single corticosteroid injection than did patients with diabetes (95.9% vs 86.7% [P = .001]). Multiple intraarticular corticosteroid injections provided no added benefit over a single injection in resolving adhesive capsulitis in patients with diabetes and nondiabetic patients. Conclusion: In shoulder adhesive capsulitis, women and patients with diabetes are more commonly affected, patients with diabetes respond less favorably to physical therapy in isolation and physical therapy plus corticosteroid injections than nondiabetic patients. No benefit from multiple intraarticular corticosteroid injections was seen compared with a single intraarticular corticosteroid injection in patients with diabetes and nondiabetic patients. Patients with diabetes and nondiabetic patients have functional improvement after capsular release and manipulation if conservative treatment for adhesive capsulitis fails. Level of Evidence: III, case control.